1991
DOI: 10.1002/pros.2990180202
|View full text |Cite
|
Sign up to set email alerts
|

Localization of type IV collagen in the basement membranes of human prostate and lymph nodes by immunoperoxidase and immunoalkaline phosphatase

Abstract: The object of these studies was to examine the localization of type IV collagen (Coll-IV) in the basement membranes (BM) of epithelial and stromal elements (smooth muscle, nerves, vessels) in normal, hyperplastic, and neoplastic (primary and metastatic) prostate. We also examined the relationship of Coll-IV distribution to the degree of tumor differentiation (Gleason grading system). We compared immunoperoxidase (IP) and immunoalkaline phosphatase (AP) techniques in these studies and in selected samples we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In the normal rat ventral prostate, we have found that both laminin and collagen type IV were localized in the welldefined basement membrane of the epithelium, consistent with the findings in human prostatic epithelium as well as other epithelia [11][12][13]. Laminin was localized in the basement membrane along all regions of the prostate ductal system, similar to what has been found in the normal human prostate, BPH, and welldifferentiated carcinomas [11].…”
Section: Discussionsupporting
confidence: 86%
“…In the normal rat ventral prostate, we have found that both laminin and collagen type IV were localized in the welldefined basement membrane of the epithelium, consistent with the findings in human prostatic epithelium as well as other epithelia [11][12][13]. Laminin was localized in the basement membrane along all regions of the prostate ductal system, similar to what has been found in the normal human prostate, BPH, and welldifferentiated carcinomas [11].…”
Section: Discussionsupporting
confidence: 86%
“…15 The staining intensity for collagen IV in the basal lamina is stronger in well-differentiated prostatic tumors than in highly aggressive ones. 31 In our investigation, staining intensities for collagen IV and laminin were significantly more intense in HARV cultures relative to its controls. This accumulation of matrix proteins is consistent with the portrayal of the HARV culture as the least aggressive in our study.…”
Section: Collagen Iv/lamininmentioning
confidence: 64%
“…We observed cat K protein in cancerous glands of approximately 40% of the primary CaP tissues tested, exhibiting no correlation with Gleason score or cancer grade. Although prostate basement membrane consists primarily of type IV collagen (36, 37) and laminin, (38, 39) Burns‐Cox et al (40) observed an increase in type I collagen synthesis and degradation at the cancer foci in biopsy specimens from patients with primary CaP. Enzymes that cleave type I collagen, such as the cathepsins and MMPs, are reported to be upregulated in CaP (17,41–46) .…”
Section: Discussionmentioning
confidence: 99%